2017
DOI: 10.4244/eij-d-16-00128
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial of paclitaxel-eluting balloon after bare metal stent implantation vs. bare metal stent in ST-elevation myocardial infarction (the PEBSI study)

Abstract: PTX-B after successful BMS implantation resulted in less LLL and better clinical outcomes as compared with a BMS-only strategy. This was associated with good stent strut coverage and very low rates of malapposed struts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…This is the first randomized study in STEMI patients comparing OCT-derived lesion healing patterns at 3-months between new-generation DES and a BMS + DCB strategy. Both strategies demonstrated excellent safety and efficacy in previous studies at 12-months [6,10]. The main finding of the present study is that at 90 days both strategies showed a very high rate of fully apposed and covered struts.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is the first randomized study in STEMI patients comparing OCT-derived lesion healing patterns at 3-months between new-generation DES and a BMS + DCB strategy. Both strategies demonstrated excellent safety and efficacy in previous studies at 12-months [6,10]. The main finding of the present study is that at 90 days both strategies showed a very high rate of fully apposed and covered struts.…”
Section: Discussionsupporting
confidence: 74%
“…Of note, DCBs ensure immediate and homogeneous drug delivery into the vessel wall without the need for implanted polymers. In a previous study [paclitaxel eluting balloon in ST-elevation myocardial infarction (PEBSI)-1], we demonstrated using optical coherence tomography (OCT) that in STEMI patients the use of a paclitaxel-DCB after a BMS implantation (BMS + DCB) achieved excellent strut coverage (99.5%) and was associated with very low rates of malapposed struts at 9 months [6]. However, whether this strategy may accelerate the strut healing before 9 months and whether this healing is superior to that obtained by current new-generation DES, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, geographical miss phenomena could have played a role in the suboptimal results. In STEMI patients, the PEBSI RCT compared a combined strategy of BMS followed by DCB (n=111) versus BMS alone (n=112) 14 . The BMS+DCB group had a lower late lumen loss (primary endpoint: 0.31 vs 0.8 mm, p<0.0001) and binary restenosis rate (2.2 vs 29.8%, p<0.0001) and, importantly, a reduced rate of MACE at one year (3.6 vs 12.5%, p=0.016) 14 .…”
Section: Previous Studies Of Dcb In Acute Myocardial Infarctionmentioning
confidence: 99%
“…In STEMI patients, the PEBSI RCT compared a combined strategy of BMS followed by DCB (n=111) versus BMS alone (n=112) 14 . The BMS+DCB group had a lower late lumen loss (primary endpoint: 0.31 vs 0.8 mm, p<0.0001) and binary restenosis rate (2.2 vs 29.8%, p<0.0001) and, importantly, a reduced rate of MACE at one year (3.6 vs 12.5%, p=0.016) 14 . More recently, the REVELATION single-centre RCT compared the use of DCB alone with new-generation DES in 120 STEMI patients 15 .…”
Section: Previous Studies Of Dcb In Acute Myocardial Infarctionmentioning
confidence: 99%
“…García-Touchard et al reported the results of an 8-year follow-up from a randomized clinical trial (PEBSI Study) with a very high percentage (97–98%) of clinical follow-up ( 1 ). The PEBSI Study was a multicenter, single-blind, randomized controlled trial involving patients experiencing their first ST-segment elevated myocardial infarction (STEMI), which revealed the benefits of paclitaxel/drug coated balloons (PCBs/DCBs) after bare-metal stent (BMS) implantation (DCB-combined strategy) compared to the outcomes associated with BMS alone (BMS-only therapy).…”
mentioning
confidence: 99%